Targeting bone metastases in metastatic castration-resistant prostate cancer - El-Amm, Joelle (2016)
Skeletal involvement in metastatic castrate-resistant prostate cancer (mCRPC) is common and results in significant morbidity and mortality. The interaction of prostate cancer with the bone microenvironment contributes to progression of cancer in the bone leading to skeletal-related events (SREs). Studies aimed at targeting the bone have been carried out over the recent years. Bisphosphonates are synthetic pyrophosphate analogs first investigated for their role in SRE prevention with zoledronic acid as the main bisphosphonate that is approved by the US Food and Drug Administration for retardation of skeletal events in men with metastatic prostate cancer. Denosumab is another bone-targeted agent against uncontrolled osteolysis and serves as a RANK ligand inhibitor, superior to zoledronic acid in delaying SREs. Radiopharmaceuticals have played a role in targeting the bone microenvironment mainly in pain palliation in mCRPC utilizing strontium or samarium in the remote past, but only radium-223 is the first radiopharmaceutical that has yielded improvement in overall survival. The combination and sequencing strategies of these agents is the subject of multiple ongoing trials to guide the best use of these emerging agents.